# If 3 – a = 6(1 – a), then find the value of ‘a’ according to this equation.

If 3 – a = 6(1 – a), then find the value of ‘a’ according to this equation.

Your questions is –

**If 3 – a = 6(1 – a), then find the value of ‘a’ according to this equation.**

**Answer Explanation:**

According to the data given in the question,

3 – a = 6(1 – a)——–i

∴ 3 – a = 6 – 6a

∴ 6a – a = 6 – 3

∴ 5a = 3

∴ a = 3/5

Hope you are clear, if you have more questions, ask here. I shall try to response as soon as possible.